1972
DOI: 10.1203/00006450-197206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Glycine and Propionic Acid in Propionic Acidemia with Ketotic Hyperglycinemia

Abstract: ExtractKetotic hyperglycinemia is a syndrome in which elevated concentrations of glycine occur in body fluids of patients who manifest life-threatening episodes of ketoacidosis very early in life. The disorder originally described under this heading is now known to be more reliably categorized by propionic acidemia than by hyperglycinemia. Studies of the metabolism of glycine and of propionate in this condition have been undertaken. Conversion of glycine-1-14 C and of propionate-1-U C to 14 CO 2 has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The coexistence of a defective activity of propionyl-CoA carboxylase (or MMA-CoA mutase, respectively) and of the glycine cleavage reaction to CO,, NH,, and a C , unit has been demonstrated both in vivo and in vitro in some other patients with propionic acidemia and methylmalonic acidemia (1,27,33). Keating et al (19) described recently a patient in whom a ketotic hyperglycinemia syndrome was associated with a defect in the isoleucine degradation pathway (presumably at the /I-ketothiolase site).…”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of a defective activity of propionyl-CoA carboxylase (or MMA-CoA mutase, respectively) and of the glycine cleavage reaction to CO,, NH,, and a C , unit has been demonstrated both in vivo and in vitro in some other patients with propionic acidemia and methylmalonic acidemia (1,27,33). Keating et al (19) described recently a patient in whom a ketotic hyperglycinemia syndrome was associated with a defect in the isoleucine degradation pathway (presumably at the /I-ketothiolase site).…”
Section: Resultsmentioning
confidence: 99%
“…Ando et al (3) studied the in vivo conversion of intravenously ' injected (~-'~~)~l~c i n e t o respiratory C 0 2 in three patients Glycine cleavage reaction consisting in oxidative cleavage of with nonketotic hyperglycinemia and three patients with glycine into methylene tetrahydrofolate U H F ) , CO2, and propionic acidemia (ketotic hyperglycinemia), N H~ has been extensively studied by Kikuchi et al (7)(8)(9)(10) in They found that all patients of both nonketotic and ketotic rat liver. In in vitro systems, the glycine cleavage reaction is type revealed an extremely low conversion of (1-1 4clglycine usually accompanied by the concomitant synthesis of serine, t o co2 as compared with that in control subjects even when a as can b e explained by t h e following Sequences of reactions.…”
Section: Jmentioning
confidence: 99%
“…These enzymes are in the pathway by which four amino acids, L-valine, L-isoleucine, L-methionine, and L-threonine are catabolized. Patients with these abnormalities present clinically with the ketotic hyperglycinemia syndrome with elevated concentrations of propionate in the blood (1)(2)(3)(4)(5)(6)(7). Two other disorders, isovaleric acidemia (8) and a-methyl-,j-hydroxybutyric aciduria (9) may also present with the ketotic hyperglycinemia syndrome.…”
Section: Introductionmentioning
confidence: 99%